The Illusion of Truth: Hyperreality approach in The Hunt (2020) - Winarno, Farhan Fauzan; Todo Sibuea (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research investigates the concept of hyperreality and simulacra as proposed by Jean Baudrillard. Hyperreality is defined as something that appears to be truer than reality itself; it is connected to simulacra, which is the representation or depiction of something or how a copy represents reality. Thus, this study qualitatively investigated the experience of hyperreality and simulacra represented in the movie The Hunt (2020). This study qualitatively examined the different elements of the film, including scenes and dialogue from the film’s trailer, intended to demonstrate how the film’s construction of hyperreality and simulacra experiences are manifested. The findings reveal the ability of the internet and media to shape awareness about what people might conceive as real, and what is not. Ultimately, this research reveals that films like The Hunt provide more than entertainment value, because they provide insight into hyperreality and simulacra, determining the dynamics between both by demonstrating how the viewer might distinguish what is real, as opposed to representation.